Dural carotid cavernous fistula following hypertensive emergency. Issue 9 (16th September 2019) - Law, Geoffrey; Docherty, Gavin
Abstract : A 58-year-old woman was referred to the outpatient ophthalmology clinic with progressive bilateral eye redness and vision loss. She had presented 2 weeks earlier with an episode of hypertensive emergency. CT angiography revealed bilateral superior ophthalmic vein (SOV) dilation, prompting further workup with a cerebral angiogram. Subsequent imaging revealed an indirect (type D) carotid-cavernous fistula (CCF) with venous drainage into both SOVs and cavernous sinuses. Successful treatment of the CCF with coil embolisation required interdisciplinary teamwork between ophthalmologists and interventional neuroradiologists. The patient made a substantial visual recovery following treatment.